The Effect of the Discovery Learning Model with a Scientific Approach on Student Representation Ability in the Buffer Solution - Tri Santoso; Dewi Satria Ahmar; Sindi Velesia Tukaedja; Aceng Haetami (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to investigate the impact of the discovery learning model with a scientific approach on students' ability to represent macroscopic, submicroscopic, and symbolic aspects of buffer solutions. This study is quantitative research of the quasi-experimental type, utilizing a one group pretest-posttest design. The sampling technique employed is saturated sampling, where the entire population in the study becomes the research sample, consisting of 44 students from Bala Keselamatan Palu High School. The instrument used to measure the three abilities of student representation employs six essay questions, with each degree of representation assessed by two questions. Prior to usage, the six questions are initially verified by an expert of chemical representation abilities. The data analysis techniques used consist of descriptive data analysis and inferential data analysis. The results of the descriptive data analysis indicate that students' representational abilities have improved after participating in learning using the discovery learning model with a scientific approach. The ability of macroscopic representation has a higher average value and percentage of achievement indicators compared to symbolic and submicroscopic representation abilities. The inferential statistical analysis results indicate that the significant value of the Wilcoxon test is 0.000. The value is smaller than the significance level of 0.05, hence it can be concluded that the discovery learning model with a scientific approach influences students' representation abilities.